Kesadaran Lingkungan dan Motivasi Berprestasi Siswa SMA Negeri I Depok Tahun 2010/2011 Dalam Kegiatan Toyota EcoYouth (TEY) - Siti Khoiriyah; Ratna Ristianti (Department of Biology Education Faculty of Teacher Training and Education Sebelas Maret Un, 2011)
ABSTRACT- It has been widely accepted that environmental degradation is caused mainly by human anthropogenic activities. Indeed, injudicious exploitation towards natural resources has caused many negative externalities. Hence, cultural efforts are needed due to prevent further degree of degradation. According to the aforementioned goals, people behavior becomes a key factor of realizing sustainable environment. And this change of behavior can be achieved through education. As pertained to the importance of education in environmental conservation Toyota has contributed to to this good programme trough the programme called the Toyota Eco-Youth (TEY). This green programme is performed towards students of SMA Negeri 1 Depok. A research about environmental awareness then is needed to assess student’s motivation to participate in the Toyota Eco Youth programme. This research is considered as a quantitative research. Questionnaire was used to collect the data from all the responden. Samples are taken randomly in a proportional manner. The collected data were descriptively analyzed by using descriptive statistic. The result of this research shows that student of SMA Negeri 1 Depok is higly motivated in performing environmentally friendly action. This condition is a good physiological capital to realize chapaign to promote a good environmenta attitude towards the youth. Keywords : Environmental attitude, Student’s motivation, Toyota Eco Youth